Mass chemoprophylaxis for control of outbreaks of meningococcal disease. Issue 9 (September 2018) - McNamara, Lucy A; MacNeil, Jessica R; Cohn, Amanda C; Stephens, David S
Summary: Although vaccination is the main strategy used to control meningococcal disease outbreaks, mass chemoprophylaxis has also been used as an immediate response to outbreaks, either to supplement vaccination or when vaccination is not possible. However, public health guidelines regarding the use of mass chemoprophylaxis for outbreak control vary by country, partly because the impact of mass chemoprophylaxis on the course of an individual outbreak is difficult to assess. We have reviewed data for the use of mass chemoprophylaxis during 33 outbreaks that occurred both in military populations and in communities and non-military organisations. In most outbreaks, no additional cases of meningococcal disease occurred after mass chemoprophylaxis, or cases occurred only in individuals who had not received prophylaxis. A delay of several weeks was common before cases occurred among prophylaxis recipients. Overall, the outbreak reports that we reviewed suggest that mass chemoprophylaxis might provide temporary protection to chemoprophylaxis recipients during outbreaks.